Indonesia - Alriani, Rita; Romadhoni, Buyung; Muchran, Muchriady (Jurnal Ekonomi Sakti, 2025)
This research is a type of quantitative research with the aim of determining the influence of internal communication and teamwork on the productivity of employees at PT. Nusantara Plantation I Regional 8 Camming Plantation Units Bone Regency. This sample was taken from PT. Nusantara Plantation I Regional 8 Camming Plantation Units Bone Regency. The type of data used in this study is quantitative data obtained from questionnaires that are shared and related to the problem being studied. Data collection was carried out by observation, distribution of questionnaires and documentation. In this study, the data sources used in data collection include primary data and secondary data. The research instrument used in this study uses the Likert scale method. Based on the results of the study using the SPSS application version 30 regarding the influence of internal communication and teamwork on employee work productivity at PT. Nusantara Plantation I Regional 8 Camming Plantation Units of Bone Regency which has been discussed from the previous chapter, the author draws an important conclusion, namely that internal communication has a positive and significant effect on employee work productivity. This means that the better internal communication is established, the more employee work productivity will also increase and teamwork has a positive and significant effect on employee work productivity. This shows that the better the teamwork, the better the peoductivity achieved. Keywords : Internal Communication, Team Work, Productivity